Smart and sustainable approaches for optimizing performance of wireless networks : real-time applications - Zafar, Sherin; Ahad, Mohd Abdul; Ali, Syed Imran; Mehta, Deepa, 1981-; Alam, Mohd Afshar (John Wiley & Sons, Inc., 2022)
"The book will focus on making the environment sustainable in the current scenario of 5G technologies. It will explore concepts of wireless sensing applications, computing technologies and their related analytics techniques involved in real time applications of healthcare, agriculture, construction and manufacturing, which all require an active generation of sustainability, digitization and intelligence which has become important in the academic world, industries, government organizations and private collaborations, etc. In recent times, the intersection of performance optimization of wireless networks with sustainable growth has not been fully exploited. The book will highlight the drawbacks of conventional technologies and methodologies utilized in networks, their associated Quality of Service (QOS) issues, case studies of present methodologies and the involvement of neoteric approaches to optimize and sustain the performance of these networks for real time applications. The book also looks at green automation, not only limited to computers with wireless and sensor-based technologies, but also disciplines such a nano-science, information technology (IT), and biochemistry, etc. The outcome is to consider sustainability and green computing, their relevance to environment and society and their applications to wireless and sensor-based networks."--